Chaplain or Sports Chaplain First?: Why Identity Formation Should Matter to Sports Chaplains - Waller, Steven N. (Practical theology, 2016)
The purpose of this essay is to discuss the importance of identity formation in the growth and development of chaplains, inclusive of sports chaplains. There is a longstanding history of how identity formation occurs with men and women who have chosen chaplaincy as a part of their vocational calling. The common beginnings for many include a point of occupational testing for vocational tendencies, engaged service in institutional settings such as in the office of a hospital chaplain. In tandem with prayer, studying the Bible of other primary source documents (if not Christian) then one may undergo a period of seeking, illumination, and then a revelation from the Creator about chaplaincy. Chaplains have multiple identities as caregivers. The foundational argument of this paper is that the proper formation of identity as a chaplain compels the individual working in this facet of ministry to see his/herself as a chaplain first and then as a sports chaplain secondarily. The identity of the chaplain impacts the manner in which he/she serves people in sports but also greatly influences the position of sports chaplains in the global community of chaplains.